2013
DOI: 10.1021/ma3020933
|View full text |Cite
|
Sign up to set email alerts
|

Structural Evolution of Ethylene–Octene Copolymers upon Stretching and Unloading

Abstract: Structural evolution of two ethylene−octene copolymers with different octene content during tensile deformation and recovery was investigated using the in-situ synchrotron small-angle X-ray scattering technique. Sample containing 4 mol % octene shows similar deformation mechanism as observed previously that the whole process of deformation can be regarded as a stretching of two interpenetrating networks of crystalline rigid network and entangled amorphous phase. A transition from a crystalline rigid network do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 50 publications
5
38
0
Order By: Relevance
“…This situation was also reported for a propylene‐based ethylene–propylene copolymer (84.3 wt % propylene content) after retarding from strain 5.0, and this may present the sum of two lamellar populations, that were, a set of tilted lamellae and a set of nontilted lamellae . It was also observed that the SAXS patterns of the ethylene–octene copolymer PEcO8 showed the same trend . Before fibrillation, the long period of PEcO8 after unloading is nearly unchanged; that is, it is fully recoverable.…”
Section: Resultssupporting
confidence: 70%
See 3 more Smart Citations
“…This situation was also reported for a propylene‐based ethylene–propylene copolymer (84.3 wt % propylene content) after retarding from strain 5.0, and this may present the sum of two lamellar populations, that were, a set of tilted lamellae and a set of nontilted lamellae . It was also observed that the SAXS patterns of the ethylene–octene copolymer PEcO8 showed the same trend . Before fibrillation, the long period of PEcO8 after unloading is nearly unchanged; that is, it is fully recoverable.…”
Section: Resultssupporting
confidence: 70%
“… ɛnormalH=0.97 normalanormalnnormald ɛnormalH=1.03 are the critical strains of the so‐called “C point” for 35D and 40D, respectively, after which the PA12 crystals fibrillate (Fig. ) . The unloaded specimens of 35D ( ɛnormalP=0.62, the 17th point) and 40D ( ɛnormalP=0.97, the 17th point) were heated to 130 and 150 °C, respectively, and all specimens can return to the original length.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Semicrystalline polymer is the representative substance with multilength‐scale structure covering from subnanometer to millimeter. For the polymorphic material, the macroscopic mechanical properties are closely linked with the microscopic modification and the molecular dynamics of formed crystallites . Polybutene‐1 (PB‐1) homopolymer and copolymers are the typical polymorphic polymers, which have different crystalline modifications of Forms I/I′, II, and III.…”
Section: Introductionmentioning
confidence: 99%